PENGARUH SUKU BUNGA KREDIT DAN INFLASI TERHADAP PENYALURAN KREDIT DENGAN RESIKO KREDIT SEBAGAI VARIABEL MODERASI - Ma’rufatur Rodhiyah; Irma Indira; Agustinus Salukh; Nurul Vidya Fortuna (LPPM Universitas Bina Bangsa, 2024)
This research was carried out to determine the effect of interest rates and inflation on credit distribution. As well as to test the effect of interest rate moderation on interest rates and inflation. The sample in this study was 47 banking companies listed on the IDX in 2019-2021 which were selected using a purposive sampling method. Data analysis techniques used descriptive statistical tests, classical assumption tests (normality test, multicollinearity test, autokerarity test, heteroscedasticity test), multiple linear regression tests, Moderated Regression Analysis (MRA) tests, and hypothesis tests (t test, coefficient of determination test) were processed using the SPSS application program version 26. The results of this research show that, credit interest rates, inflation have no effect on credit distribution, credit risk has no effect on credit distribution and the results of the research show that credit risk is unable to moderate credit interest rates and inflation on credit distribution to companies banks listed on the Indonesian Stock Exchange in 2019-2021.